Ceramic evaporation target material, preparation method thereof and photovoltaic cell

By pre-pressing the ceramic powder into blanks with different density and stacking them, the problems of uneven density distribution and poor thermal conductivity of ceramic evaporation targets were solved, and ceramic evaporation targets with uniform density and good thermal conductivity were prepared.

CN119143510BActive Publication Date: 2025-02-07SHENZHEN APG MATERIAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411657289.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-07
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Existing ceramic evaporation targets have problems with uneven density distribution and poor thermal conductivity.

Method used

By pre-pressing the mixed ceramic powder into blanks with different density, and laminating them in the order of decreasing density from the middle to both ends, performing bidirectional pressure combo treatment and high-temperature sintering to prepare a ceramic evaporation target with uniform density.

Benefits of technology

The uniform density distribution and thermal conductivity of ceramic evaporation targets are achieved, and the density of the middle part of the blank and the density of both end parts is small in traditional methods is avoided, and the service life of the target is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143510B_ABST
    Figure CN119143510B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of target material preparation, and provides a ceramic evaporation target material and a preparation method thereof and a photovoltaic cell, including: pre-pressing a mixed ceramic powder into a plurality of green bodies with different densities; stacking the green bodies in the order of decreasing density from the middle to the two ends to obtain a composite green body; subjecting the composite green body to a bidirectional pressing treatment to obtain a superimposed green body; and subjecting the superimposed green body to high-temperature sintering to obtain a ceramic target material. The present application stacks the green bodies in the order of decreasing density from the middle to the two ends, so that the density of the middle part of the composite green body is greater than that of the two ends, and compensates for the density difference caused by the pressure applied to the middle part of the composite green body due to the bidirectional pressing being smaller than that of the two ends, so that the density distribution of the superimposed green body is uniform, so that the ceramic evaporation target material has uniform density and good thermal conductivity. Moreover, the target green body connection surface formed by the superposition of multiple green bodies can block the longitudinal transmission of target material cracks and prevent heat from being transmitted longitudinally to the center of the target material during the coating process, thereby preventing the target material structure from collapsing or powder splashing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of target material preparation, and in particular relates to a ceramic evaporation target material and a preparation method thereof, and a photovoltaic cell. Background Art

[0002] Evaporation coating is an important physical vapor deposition technology, which includes thermal evaporation deposition (TD), electron beam evaporation deposition (EBD) and reactive plasma evaporation (RPD). RPD coating has the advantages of less damage to the substrate, fast deposition rate and good film quality, and has been promoted and applied in many fields.

[0003] Ceramic materials have the characteristics of good chemical stability, excellent photoelectric performance, high temperature resistance and wear resistance, and are widely used in photovoltaic cells, semiconductor chips, flat panel displays and optics. The common preparation process of ceramic targets includes powder pretreatment, granulation, molding and sintering. Among them, molding is an important link in the preparation of ceramic targets, and the quality of the molded body directly affects the performance of the target.

[0004] At present, ceramic targets for RPD coating are usually formed by compression molding, which fills the granulated powder in the mold and then presses it into a green body. Compression molding includes two methods: unidirectional pressing and bidirectional pressing. However, during unidirectional pressing, the pressure is transmitted to the inner layer through the dense layer close to the pressure head, which will gradually decrease as the pressure head advances, and part of the pressure will be transmitted to the mold wall by the pressure head, so that there will be an obvious pressure gradient in the vertical direction of the green body, resulting in different densities of the green body at different heights and cross-sections. Although bidirectional pressing can reduce the pressure gradient by applying pressure from top to bottom, shortening the pressure transmission distance, it will cause the powder displacement at the upper and lower ends of the green body to be larger, while the powder displacement in the middle part is smaller. In addition, the friction force of the side wall reduces the pressure transmitted to the middle part of the green body, resulting in a lower density in the middle part of the green body than at the two ends, which will eventually affect the density distribution and thermal conductivity of the ceramic target. Summary of the invention

[0005] The purpose of the present application is to provide a ceramic evaporation target material and a preparation method thereof and a photovoltaic cell, aiming to solve the problems of uneven density distribution and poor thermal conductivity of existing ceramic targets.

[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0007] In a first aspect, the present application provides a method for preparing a ceramic evaporation target, comprising the following steps:

[0008] Pre-pressing the mixed ceramic powder into a plurality of green bodies with different densities;

[0009] The green bodies are stacked in the order of decreasing density from the middle to both ends to obtain a composite green body;

[0010] The composite green body is subjected to a bidirectional pressing process to obtain a laminated green body;

[0011] The laminated green blank is sintered at high temperature to obtain a ceramic target.

[0012] In a second aspect, the present application provides a ceramic evaporation target, including a ceramic evaporation target prepared by the method for preparing a ceramic evaporation target provided by the present application.

[0013] In a third aspect, the present application provides a photovoltaic cell, comprising a functional layer, wherein the functional layer is obtained by reactive plasma deposition coating of the ceramic evaporation target provided by the present application.

[0014] Compared with the prior art, this application has the following beneficial effects:

[0015] (1) The green bodies are stacked in the order of decreasing density from the middle to the two ends, so that the density of the middle part of the composite green body is greater than that of the two ends. This can compensate for the density difference caused by the fact that the pressure applied to the middle part of the composite green body is smaller than that of the two ends during the two-way pressing process, so that the density distribution of the formed green body is uniform, and avoid the situation in which the density of the middle part of the green body is lower and the density of the two ends is higher due to the traditional method of one-piece pressing. Therefore, the ceramic evaporation target prepared in this application has a uniform density distribution and good thermal conductivity, which can better prevent the target material from cracking.

[0016] (2) By stacking multiple blanks to form a target blank interface, the longitudinal transmission of target cracks can be blocked during the coating process, thereby preventing the target material structure from collapsing or powder splashing. Therefore, the target material has good film quality and long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 is a process flow chart of a method for preparing a ceramic evaporation target provided in an embodiment of the present application;

[0019] Figure 2 It is a schematic diagram of the structure of each blank before stacking provided in Example 1 of the present application. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0021] The first aspect of the present application provides a method for preparing a ceramic evaporation target material, such as Figure 1 As shown, the following steps are included:

[0022] S01: pre-pressing the mixed ceramic powder into a plurality of green bodies with different densities;

[0023] S02: stacking the green bodies in the order of decreasing density from the middle to both ends to obtain a composite green body;

[0024] S03: The composite green body is subjected to a bidirectional pressing process to obtain a laminated green body (such as Figure 2 shown);

[0025] S04: sintering the laminated green blanks at high temperature to obtain a ceramic target.

[0026] The preparation method of the ceramic evaporation target provided in the embodiment of the present application is to stack the blanks in the order of decreasing density from the middle to the two ends, so that the density of the middle part of the composite blank is greater than that of the two ends, which can compensate for the density difference caused by the pressure applied to the middle part of the composite blank in the two-way pressing process being smaller than that of the two ends, so that the density distribution of the formed blank is uniform, and the situation that the density of the middle part of the blank is smaller and the density of the two ends is larger due to the one-piece pressing molding in the traditional method is avoided. Therefore, the ceramic evaporation target prepared in the present application has uniform density distribution, good thermal conductivity, and can better prevent the cracking of the target. In addition, the target blank interface can be better prevented from cracking in the longitudinal direction during the coating process by stacking multiple blanks, thereby preventing the collapse of the target structure or the splashing of powder, so the target has good film quality and long service life.

[0027] In the above step S01, in the embodiment, the mixed ceramic powder includes a main powder and a doping powder; the main powder is selected from any one of indium oxide powder, zinc oxide powder, tin oxide powder, nickel oxide powder, and zirconium oxide powder; the doping powder is selected from one or more of tungsten oxide powder, molybdenum oxide powder, niobium oxide powder, tantalum oxide powder, titanium oxide powder, silicon oxide powder, aluminum oxide powder, gallium oxide powder, magnesium oxide powder, and lanthanum rare earth oxide powder. The lanthanum rare earth oxide powder is selected from one or more of cerium oxide powder, lanthanum oxide powder, yttrium oxide powder, lutetium oxide powder, samarium oxide powder, and praseodymium oxide powder.

[0028] In the embodiment, the steps of preparing the mixed ceramic powder include: ball milling the doped powder, part of the main powder, the dispersant and the solvent, then adding the binder and mixing them evenly to obtain a second mixed slurry; drying the second mixed slurry and calcining it to obtain a solid solution powder; mixing the remaining part of the main powder with the solid solution powder to obtain a mixed ceramic powder. The calcination temperature is 600-1500°C and the insulation time is 6-12h. The dispersant is selected from polyethylene glycol, the binder is selected from polyvinyl alcohol, the solvent is selected from ethanol and / or water, and the added amount of the dispersant and the binder is 0.1-1% of the total mass of the doped powder, part of the main powder and the dispersant.

[0029] In an embodiment, the step of mixing the rest of the main powder with the solid solution powder comprises: uniformly mixing the rest of the main powder, the solid solution powder, polyethylene glycol and water, and then drying to obtain a mixed ceramic powder.

[0030] In an embodiment, the particle size of the main powder is 1-50 μm, preferably 1-10 μm.

[0031] In an embodiment, the particle size of the doping powder is 1-50 μm, preferably 1-10 μm.

[0032] In an embodiment, the particle size of the solid solution powder is 0.2-0.8 μm, preferably 0.3-0.6 μm.

[0033] In the embodiment, the mass ratio of the main powder to the doping powder is (85.0~99.9) / (0.1~15.0).

[0034] In the embodiment, the solid solution powder accounts for 20-30% of the mass of the mixed ceramic powder, that is, the solid solution powder is composed of the doping powder and the main powder in a mass ratio of (0.1-15.0) / (15.0-19.9).

[0035] In the embodiment, the length of the blank is 4-30 mm, preferably 4.2-10.5 mm.

[0036] In an embodiment, the step of pre-pressing the mixed ceramic powder into a plurality of green bodies with different densities may include: respectively loading the mixed ceramic powder into a mold, and then using a press to perform bidirectional pressurization on the powder to form a plurality of green bodies with different densities. The relative density of the green body is 49-57%, for example, it can be pressed into a green body with relative densities of 49.0%, 50.3%, 51.2%, 50.3%, and 49.0%, respectively; or pressed into a green body with relative densities of 56.0%, 57.4%, 58.3%, 57.4%, and 56.0%, respectively; or pressed into a green body with relative densities of 51.9%, 53.0%, 53.8%, 54.4%, 54.4%, 53.8%, 53.0%, and 51.9%, respectively. If the relative density of a single-piece blank is too low, it cannot completely compensate for the density difference caused by the pressure applied to the middle part of the composite blank during the two-way pressing process being smaller than that at the two ends, resulting in uneven density distribution of the formed blank. If the relative density of a single-piece blank is too high, stratification is likely to occur after two-way pressing, thereby affecting the thermal conductivity of the target material. Therefore, the relative density range of the blank in this embodiment is conducive to stacking and pressing multiple blanks to obtain a blank with uniform density distribution, so that the target material has uniform density distribution and good thermal conductivity.

[0037] In the above-mentioned step S02, in the embodiment, the step of stacking the green bodies in the order of decreasing density from the middle to the two ends also includes: preparing the mixed ceramic powder into a first mixed slurry; coating the first mixed slurry between the connecting surfaces of the green bodies, and / or coating the first mixed slurry on the sides of the composite green bodies, and then drying them.

[0038] In an embodiment, Figure 2 As shown, at least one of the upper and lower surfaces of the blank is provided with a plurality of circular holes, and the surface provided with the circular holes is used for coating the first mixed slurry. The powder to be formed can be pressurized by a pressing head with a protrusion, so that at least one surface of the blank is formed with a plurality of symmetrically distributed circular holes, so that the surface provided with the circular holes is used as a connecting surface for coating the first mixed slurry, and after drying and high-temperature sintering, a structure similar to a clamping connection can be formed, thereby improving the bonding strength of each layer of the target blank and preventing each layer of the target blank from falling off.

[0039] Among them, the diameter of the circular hole is ≤3.0mm, preferably 0.3~1.0mm, the depth is ≤2.0mm, preferably 0.1~0.5mm; the number of circular holes is 3~20, preferably 3~10. If the diameter and depth of the circular hole are too large, it is easy to cause the hole to be too large after drying and high-temperature sintering, and it is easy to cause powder to fall off or splash during coating. If the diameter and depth of the circular hole are too small, the effect of improving the bonding strength of each layer of the target blank is not good. Therefore, the diameter and depth range of the circular hole can better improve the bonding strength of each layer of the target blank.

[0040] In an embodiment, the step of preparing a mixed ceramic powder into a first mixed slurry comprises: ball-milling and mixing ethylene glycol butyl ether acetate, butyl carbitol, dodecyl alcohol ester, and the mixed ceramic powder, and then adding ethyl cellulose and dimethyl silicone oil and mixing evenly to obtain a first mixed slurry; wherein the mass ratio of the mixed ceramic powder, ethylene glycol butyl ether acetate, butyl carbitol, dodecyl alcohol ester, ethyl cellulose, and dimethyl silicone oil is (30~40) / (10~15) / (10~20) / (15~25) / (5~15) / (0.5~5). The ratio of the raw materials of each component of the first mixed slurry can ensure that the first mixed slurry has a low solid content and a high viscosity, which is conducive to coating to form a uniform slurry layer, and the density of the bonding layer formed after high-temperature sintering is lower than that of the target blank, so that the bonding layer constitutes a non-close-packed surface, and the target blank constitutes a close-packed surface. Since heat tends to transfer to the close-packed surface, the heat is transferred to the entire cross-section of the target material during the coating process, avoiding the longitudinal transfer of heat to the center of the target material and causing the target material to sag downward. Therefore, the target structure can be well prevented from collapsing or powder splashing, and the film forming quality is good and the service life is long.

[0041] In an embodiment, the particle size of the solid particles in the first mixed slurry is 0.5-20 μm.

[0042] In an embodiment, the viscosity of the first mixed slurry is 1000~15000cps, preferably 7000~15000cps. This viscosity range is conducive to coating to form a uniform slurry layer, and makes the relative density of the bonding layer formed after high-temperature sintering be 40~50%, which is lower than the density of the target blank, and creates a longitudinal non-close-packed surface, which is beneficial to the heat transfer to the entire cross-section of the target material during the coating process.

[0043] The step of coating the first mixed slurry between the connecting surfaces of the blanks may include: coating the first mixed slurry on the upper surface of the first blank to form a first slurry layer, and then laminating the second blank on the first slurry layer, and then coating the first mixed slurry on the upper surface of the second blank to form a second slurry layer, and then laminating the third blank on the second slurry layer, and then coating the first mixed slurry on the upper surface of the third blank to form a third slurry layer, and so on, until the Nth blank is laminated on the N-1th slurry layer, and finally drying to obtain a composite blank; wherein N can be 4~10. The first mixed slurry coated between the connecting surfaces of the blanks can play a buffering role after drying, prevent the blanks from cracking during the two-way pressing process, and improve the product yield; and the bonding layer formed by high-temperature sintering, on the one hand, can block the longitudinal transfer of target cracks during the coating process, and transfer heat to the entire cross-section of the target during the coating process, preventing heat from being transferred longitudinally to the center of the target material and causing the target material to sag downward, thereby preventing the target material structure from collapsing or powder splashing. Therefore, the target material has good film quality and long service life. On the other hand, it can also play a bonding role, so that the interfaces of each blank are densely bonded and have high bonding strength, preventing the target material from being delaminated, thereby ensuring the thermal conductivity of the ceramic target.

[0044] Coating the first mixed slurry on the side of the composite body can not only reduce the defects on the periphery of the interface of each body, make the interface of each piece of the body denser and the bonding strength stronger, thereby improving the thermal conductivity of the target material, but also solve the problem of uneven shrinkage of each piece of the body caused by high-temperature sintering, which affects the uneven side of the target material. Therefore, the target interface is well bonded and the side is flat and intact.

[0045] In the embodiment, the thickness of the first mixed slurry coated between the connecting surfaces of the green body is 0.2-0.4 mm, preferably 0.2-0.3 mm. The thickness of the first mixed slurry coated on the side of the composite green body is 0.5-2 mm, preferably 0.8-1.5 mm.

[0046] In the embodiment, the relative density difference between adjacent green bodies in the composite green body is 0.2-2%, preferably 0.2-1%. This relative density difference range is conducive to lamination to form a laminated green body with uniform density distribution.

[0047] In the embodiment, the number of green bodies in the composite green body is 4 to 10.

[0048] In the above step S03, in the embodiment, the relative density of the laminated green billet is 52-61%. The relative density range of the laminated green billet in this embodiment is conducive to the subsequent sintering to form a ceramic target material with suitable density, thereby preventing problems such as target material splashing dust, structural collapse and cracking.

[0049] In the above step S04, in the embodiment, the high temperature sintering temperature is 900-1500° C., and the holding time is 12-36 hours. The sintering temperature and holding time range are conducive to the formation of a ceramic target with a relative density of 55-65% from the green blank.

[0050] In the embodiment, the ceramic target is a cylindrical target with a thickness-to-diameter ratio greater than 1 / 1, where the thickness-to-diameter ratio refers to the ratio of the thickness of the cylindrical target to its diameter. When the thickness-to-diameter ratio of the cylindrical target is greater than 1 / 1, the pressing method using one-piece molding is prone to uneven density distribution, which will affect the thermal conductivity of the target, thereby causing the target structure to collapse and powder to splash, affecting the film quality.

[0051] A second aspect of the embodiments of the present application provides a ceramic evaporation target, including a ceramic evaporation target prepared by the method for preparing a ceramic evaporation target provided by the embodiments of the present application.

[0052] The ceramic evaporation target material provided in the embodiment of the present application is prepared by the preparation method provided in the embodiment of the present application, so the target material has uniform density distribution and good thermal conductivity, which can better prevent the target material from cracking. In addition, the target blank interface formed by pressing multiple blanks together can block the longitudinal transmission of target material cracks and prevent the longitudinal transmission of heat to the center of the target material, thereby preventing the target material structure from collapsing or powder splashing. Therefore, the target material has good film quality and long service life.

[0053] A third aspect of an embodiment of the present application provides a photovoltaic cell, comprising a functional layer, wherein the functional layer is obtained by reactive plasma deposition coating of the ceramic evaporation target provided by the present application.

[0054] The photovoltaic cell provided in the embodiment of the present application has a functional layer obtained by reactive plasma deposition coating of the ceramic evaporation target provided in the present application, so the functional film layer has good quality and can effectively improve the overall performance of the photovoltaic cell.

[0055] In an embodiment, the functional layer may be a transparent conductive film layer, an electron transport layer, a hole transport layer, or the like.

[0056] The following describes the invention in conjunction with specific embodiments.

[0057] Example 1

[0058] This embodiment provides a method for preparing a ceramic evaporation target, comprising the following steps:

[0059] S11: according to the mass ratio of indium oxide powder to cerium oxide powder of 97 / 3, weigh appropriate amounts of indium oxide powder (D50=8μm) and cerium oxide powder (D50=8μm);

[0060] The cerium oxide powder, part of the indium oxide powder, polyethylene glycol and water are ball-milled, and then polyvinyl alcohol is added and mixed uniformly to obtain a second mixed slurry; the second mixed slurry is filtered and dried at 80°C, and then calcined at 750°C for 8h to obtain a solid solution powder (D50=0.5μm); wherein the addition amount of polyethylene glycol and polyvinyl alcohol is 0.6% of the total mass of the cerium oxide powder and part of the indium oxide powder;

[0061] The remaining indium oxide powder, solid solution powder, polyethylene glycol and water are mixed evenly, and then the moisture content is dried to less than 2%, crushed and sieved to obtain a mixed ceramic powder; wherein the solid solution powder accounts for 25% of the mass of the mixed ceramic powder, and the solid solution powder contains indium oxide powder and cerium oxide powder in a mass ratio of 22 / 3;

[0062] S12: The mixed ceramic powders are respectively loaded into stainless steel molds, and then the powders are simultaneously bidirectionally pressurized by a press to obtain green bodies with relative densities of 52.9%, 54.1%, 55.0%, 54.1%, and 52.9%, respectively;

[0063] S13: using a planetary ball mill to mix ethylene glycol butyl ether acetate, butyl carbitol, dodecyl alcohol ester, and mixed ceramic powder, and then adding ethyl cellulose and dimethyl silicone oil to mix evenly to obtain a first mixed slurry; wherein the mass ratio of the mixed ceramic powder, ethylene glycol butyl ether acetate, butyl carbitol, dodecyl alcohol ester, ethyl cellulose, and dimethyl silicone oil is 35 / 13 / 17 / 20 / 12 / 3; the particle size of the solid particles in the first mixed slurry is 1-3 μm, and the viscosity is 12500 cps;

[0064] According to the order of decreasing density of the green body from the middle to the two ends, the first mixed slurry is coated on the upper surface of the first green body (52.9%) to form a first slurry layer, and then the second green body (54.1%) is stacked on the first slurry layer, and then the first mixed slurry is coated on the upper surface of the second green body to form a second slurry layer, and then the third green body (55.0%) is stacked on the second slurry layer, and then the first mixed slurry is coated on the upper surface of the third green body to form a third slurry layer, and so on, until the fifth green body (52.9%) is stacked on the fourth slurry layer (thickness of 0.3 mm) to obtain a composite green body; the first mixed slurry (thickness of 1 mm) is coated on the side of the composite green body, and then dried in an oven at 80°C;

[0065] S14: loading the composite green body into a mold, and then using a press to simultaneously apply bidirectional pressure to the composite green body to obtain a laminated green body;

[0066] S15: placing the green blank in a high pressure sintering furnace, starting to increase the temperature to 1200° C. and maintaining the temperature for 18 hours to obtain a ceramic evaporation target.

[0067] Example 2

[0068] This embodiment provides a method for preparing a ceramic evaporation target, which is different from Embodiment 1 in that:

[0069] In step S12, one of the pressing heads of the press has five protrusions with a diameter of 0.8 mm and a length of 0.4 mm, and one surface of each blank obtained has five circular holes with a diameter of 0.8 mm and a depth of 0.4 mm symmetrically distributed;

[0070] In step S13, when stacking, the surfaces with round holes in the first to fourth sheets face upward and are used to apply the first mixed slurry, and the surface with round holes in the fifth sheet faces downward and is applied with the first mixed slurry (such as Figure 2 as shown).

[0071] Example 3

[0072] This embodiment provides a method for preparing a ceramic evaporation target, which is different from Embodiment 1 in that:

[0073] Step S11, the composition of the mixed ceramic powder is changed to indium oxide powder / tungsten oxide powder / tin oxide powder with a mass ratio of 98.9 / 1.0 / 0.1.

[0074] Comparative Example 1

[0075] This comparative example provides a method for preparing a ceramic evaporation target material, which differs from Example 1 in that:

[0076] Steps S12 to S14 are replaced by: loading the mixed ceramic powder into a stainless steel mold, and then using a press to simultaneously perform bidirectional pressurization on the powder to obtain a green blank.

[0077] Comparative Example 2

[0078] This embodiment provides a method for preparing a ceramic evaporation target, which is different from Embodiment 1 in that:

[0079] In step S13, the connecting surfaces of the green bodies are not coated with the first mixed slurry, but green bodies with relative densities of 52.9%, 54.1%, 55.0%, 54.1%, and 52.9% are directly stacked in sequence.

[0080] Comparative Example 3

[0081] This embodiment provides a method for preparing a ceramic evaporation target, which is different from Embodiment 1 in that:

[0082] Step S13: The first mixed slurry is not coated on the side of the composite body.

[0083] Comparative Example 4

[0084] This comparative example provides a method for preparing a ceramic evaporation target material, which differs from Example 1 in that:

[0085] Step S12, respectively loading the mixed ceramic powders into stainless steel molds, and then using a press to simultaneously perform bidirectional pressurization on the powders to obtain green bodies with relative densities of 50.4%, 52.9%, 55.0%, 52.9%, and 50.4%, respectively.

[0086] Comparative Example 5

[0087] This comparative example provides a method for preparing a ceramic evaporation target material, which differs from Example 1 in that:

[0088] Step S12, respectively loading the mixed ceramic powder into stainless steel molds, and then using a press to simultaneously perform bidirectional pressurization on the powder to obtain green bodies with relative densities of 45.0%, 46.3%, 47.2%, 46.3%, and 45.0%, respectively.

[0089] Comparative Example 6

[0090] This comparative example provides a method for preparing a ceramic evaporation target material, which differs from Example 1 in that:

[0091] Step S12, respectively loading the mixed ceramic powder into stainless steel molds, and then using a press to simultaneously perform bidirectional pressurization on the powder to obtain green bodies with relative densities of 61.0%, 62.3%, 63.2%, 62.3%, and 61.0%, respectively.

[0092] Related performance test analysis:

[0093] 1. After the target material is plastic-sealed, the density of the ceramic evaporation target materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6 is tested by using the Archimedes density test method; specifically, the ceramic evaporation target material is cut into 5 sections along its cross section, and then the actual density of each section is tested, and the relative density of each section is calculated based on the theoretical density;

[0094] Among them, median uniformity = [(max-min) ÷ (max+min)] × 100%.

[0095] 2. Check with naked eyes whether there are cracks on the sides of the ceramic evaporation targets prepared in Examples 1 to 3 and Comparative Examples 1 to 6.

[0096] The test results are shown in Table 1:

[0097] Table 1

[0098]

[0099] It can be seen from Table 1 that the uniformity of the median relative density of each section of the ceramic evaporation target materials prepared in Examples 1 to 3 is small, while the uniformity of the median relative density of each section of the ceramic evaporation target materials prepared in Comparative Examples 1, 4 and 5 is large, indicating that the embodiments of the present application can compensate for the density difference caused by the two-way pressing because the pressure applied to the middle part of the composite green body is smaller than that at the two ends by stacking the green bodies in the order of decreasing density from the middle to the two ends and then pressing them in both directions, so that the density distribution of the formed green body is uniform, and thus the density distribution of the target material is uniform after high-temperature sintering.

[0100] In contrast, in Example 1, the density difference caused by the smaller pressure applied to the middle of the composite body than at the two ends could not be compensated, resulting in the target material density being smaller in the middle and larger at the two ends, resulting in greater uniformity of the median density.

[0101] The median uniformity of the relative density of each segment of the ceramic evaporation target prepared in Comparative Example 4 is relatively large, which is mainly due to the large relative density deviation between adjacent green bodies in the composite green body, and the mismatch in density caused by the pressure applied to the middle part of the composite green body being smaller than that at the two ends.

[0102] The median uniformity of the relative density of each segment of the ceramic evaporation target prepared in Comparative Example 5 is relatively large. This is mainly because the relative density of the green body is too low, and the density variation of each piece of green body is relatively large during bidirectional pressing, which makes it impossible to compensate for the density deviation caused by the pressure applied to the middle part of the composite green body being smaller than that at the two ends.

[0103] The ceramic evaporation targets prepared in Examples 1 to 3 have no cracks, while the ceramic evaporation targets prepared in Comparative Examples 2 to 3 and 6 have evenly distributed cracks on their sides, indicating that in the embodiments of the present application, a first mixed slurry is coated between the connecting surfaces of the green bodies to form a slurry layer, which plays a buffering role and prevents cracks from occurring in the green body during the pressing process; and the first mixed slurry is coated on the side of the composite green body, so that the shrinkage of the composite green body during the sintering process tends to be consistent, which can inhibit the occurrence of cracks.

[0104] Comparative Example 6 has a small amount of cracks, which is mainly because the density of the blank is too high, and delamination occurs after stacking and bidirectional pressing, which leads to cracks in the target material.

[0105] 3. The ceramic evaporation target materials prepared in Examples 1-2 and Comparative Examples 1-3 were deposited on the photovoltaic cell precursor using RPD coating equipment, and then metal electrodes were prepared to assemble the photovoltaic cell; wherein the photovoltaic cell precursor is composed of a p-type non-silicon layer, a first intrinsic non-silicon layer, a silicon wafer, a second intrinsic non-silicon layer, and an n-type non-silicon layer stacked in sequence. The conversion efficiency of the photovoltaic cell was tested (with Comparative Example 1 as the benchmark (BSL), and the test value is the increase or decrease value relative to Comparative Example 1). The test results are shown in Table 2 below:

[0106] Table 2

[0107]

[0108] It can be seen from Table 2 that the conversion efficiency of the photovoltaic cell corresponding to Example 1 is significantly higher than that of Comparative Examples 1 to 3. This is mainly because the embodiment of the present application stacks the green bodies in the order of decreasing density from the middle to the two ends, and then presses them in both directions, which compensates for the density difference caused by the pressure in the middle part of the composite green body being smaller than that at the two ends, so that the density distribution of the ceramic target material is uniform, and the interface formed by pressing multiple green bodies together can prevent structural collapse or powder splashing when the target material is coated, so that the film quality is good, thereby improving the conversion efficiency of the photovoltaic cell.

[0109] The conversion efficiency of the photovoltaic cell corresponding to Example 1 is significantly higher than that of Example 2. This is mainly because there are circular holes distributed on the surface of the blank, which serve as a connecting surface. After coating the first mixed slurry, drying and high-temperature sintering, a snap-on structure can be formed, which makes the bonding strength of each layer of the target blank higher and can better prevent the powder from falling off or splashing, so the conversion efficiency of the battery is higher.

[0110] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. For example, the ceramic evaporation target of the present application can also be used in the fields of thermal barrier coatings, LED chips, etc., and it also has an enlightening effect on thermal barrier coatings and LED chips. Therefore, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A method for preparing a ceramic evaporation target, characterized in that: The following steps are involved: Pre-pressing the mixed ceramic powder into a plurality of green bodies with different densities; at least one of the upper surface and the lower surface of the green body is provided with a plurality of circular holes, and the surface provided with the circular holes is used for coating the first mixed slurry; the diameter of the circular holes is ≤3.0 mm, and the depth is ≤2.0 mm; the relative density of the green body is 49-57%; The mixed ceramic powder is prepared into a first mixed slurry having a viscosity of 1000-15000 cps; In the order of decreasing density of the green body from the middle to the two ends, the first mixed slurry is coated on the upper surface of the first green body to form a first slurry layer, and then the second green body is stacked on the first slurry layer, and then the first mixed slurry is coated on the upper surface of the second green body to form a second slurry layer, and then the third green body is stacked on the second slurry layer, and then the first mixed slurry is coated on the upper surface of the third green body to form a third slurry layer, and so on, until the Nth green body is stacked on the N-1th slurry layer, and finally a composite green body is obtained by drying; N is 4 to 10; the relative density difference between adjacent green bodies in the composite green body is 0.2 to 2%; Applying the first mixed slurry on the side of the composite body and then drying it; The composite green body coated with the first mixed slurry and dried is subjected to a bidirectional pressing process to obtain a laminated green body; The laminated green blank is subjected to high temperature sintering at a temperature of 900-1500° C. to obtain a ceramic target; The relative density of the bonding layer formed by high-temperature sintering of the first slurry layer, the second slurry layer, the third slurry layer ... the N-1 slurry layer is 40-50%; The relative density of the ceramic target is 55-65%.

2. The preparation method according to claim 1, characterized in that The step of preparing the mixed ceramic powder into a first mixed slurry comprises: mixing ethylene glycol butyl ether acetate, butyl carbitol, dodecyl alcohol ester, and the mixed ceramic powder by ball milling, and then adding ethyl cellulose and dimethyl silicone oil and mixing them evenly to obtain a first mixed slurry; wherein the mass ratio of the mixed ceramic powder, ethylene glycol butyl ether acetate, butyl carbitol, dodecyl alcohol ester, ethyl cellulose, and dimethyl silicone oil is (30-40) / (10-15) / (10-20) / (15-25) / (5-15) / (0.5-5); And / or, the particle size of the solid particles in the first mixed slurry is 0.5-20 μm.

3. The preparation method according to claim 1, characterized in that: The number of the circular holes is 3 to 20.

4. The preparation method according to claim 1, characterized in that: At least one of the following conditions is met: The ceramic target is a cylindrical target with a thickness-to-diameter ratio greater than 1 / 1, where the thickness-to-diameter ratio refers to the ratio of the thickness of the cylindrical target to its diameter; The holding time of the high temperature sintering is 12 to 36 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that The mixed ceramic powder includes main powder and doping powder; The main powder is selected from any one of indium oxide powder, zinc oxide powder, tin oxide powder, nickel oxide powder and zirconium oxide powder; The doping powder is selected from one or more of tungsten oxide powder, molybdenum oxide powder, niobium oxide powder, tantalum oxide powder, titanium oxide powder, silicon oxide powder, aluminum oxide powder, gallium oxide powder, magnesium oxide powder and lanthanide rare earth oxide powder; The lanthanide rare earth oxide powder is selected from one or more of cerium oxide powder, lanthanum oxide powder, lutetium oxide powder, samarium oxide powder and praseodymium oxide powder.

6. The preparation method according to claim 5, characterized in that: The steps of preparing the mixed ceramic powder include: The doping powder, part of the main powder, a dispersant and a solvent are ball-milled, and then a binder is added and mixed uniformly to obtain a second mixed slurry; The second mixed slurry is dried and then calcined to obtain a solid solution powder; The remaining part of the main powder is mixed with the solid solution powder to obtain a mixed ceramic powder.

7. The preparation method according to claim 6, characterized in that: At least one of the following conditions is met: The particle size of the main powder is 1-50 μm; The particle size of the doped powder is 1-50 μm; The particle size of the solid solution powder is 0.2-0.8 μm; The mass ratio of the main powder to the doped powder is (85.0-99.9) / (0.1-15.0); The solid solution powder accounts for 20-30% of the mass of the mixed ceramic powder; The calcination treatment temperature is 600-1500° C., and the heat preservation time is 6-12 hours.

8. A ceramic evaporation target, characterized in that: A ceramic evaporation target material prepared by the method for preparing a ceramic evaporation target material according to any one of claims 1 to 7.

9. A photovoltaic cell comprising a functional layer, characterized in that: The functional layer is obtained by subjecting the ceramic evaporation target material according to claim 8 to reactive plasma deposition coating.

Citation Information

Patent Citations

  • Flat plate-type ceramic package radiating module for high-power LED and manufacturing method thereof

    CN101980389A

  • Preset-interface hot-pressing bulletproof ceramic plate and preparation method thereof

    CN109534827A

  • Manufacturing ceramic articles

    CN1170473A